2019
DOI: 10.1371/journal.pone.0207785
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum and saliva miRNAs for identification and characterization of mTBI in adult mixed martial arts fighters

Abstract: Traumatic brain injury (TBI) is a major cause of death and disability worldwide, with mild TBI (mTBI) accounting for 85% of cases. mTBI is also implicated in serious long-term sequelae including second impact syndrome and chronic traumatic encephalopathy. mTBI often goes undiagnosed due to delayed symptom onset and limited sensitivity of conventional assessment measures compared with severe TBI. Current efforts seek to identify accurate and reliable non-invasive biomarkers associated with functional measures r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 44 publications
3
60
0
Order By: Relevance
“…Balance was also assessed for a portion of participants (n = 321; mTBI = 176 and control = 145) using the validated ClearEdge system 42,43 (Quadrant Biosciences Inc, Syracuse, NY), as we have previously reported. 39…”
Section: Balance Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Balance was also assessed for a portion of participants (n = 321; mTBI = 176 and control = 145) using the validated ClearEdge system 42,43 (Quadrant Biosciences Inc, Syracuse, NY), as we have previously reported. 39…”
Section: Balance Assessmentmentioning
confidence: 99%
“…RNA was isolated from each saliva sample using the miRNeasy Kit (Qiagen, Inc, Germantown, MD) according to the manufacturer's instructions, as we have previously described. 39 RNA quality was assessed using the Agilent Technologies Bioanalyzer on the RNA Nanochip. RNA-sequencing libraries were prepared using the TruSeq Stranded Small RNA Kit (Illumina) according to manufacturer instructions.…”
Section: Salivary Ncrna Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we showed that perturbation in miRNA signaling after traumatic brain injury results in overlapping miRNA profiles in cerebrospinal fluid and saliva [ 31 ]. Further, we demonstrated that disruptions in salivary miRNA levels can persist for weeks after initial injury [ 32 ], and predict the occurrence of persistent post-concussive symptoms [ 33 ]. The purpose of the current study was to determine whether non-invasive salivary measurement of miRNAs could provide insights into the pathobiology of repetitive concussions among professional football athletes.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal stability of blood-based biomarkers is increasingly being recognised as a potential limitation to their routine clinical use. Thus, non-protein based biomarkers such as microRNAs may be better suited for the prediction of outcome following mTBI [116][117][118][119].…”
Section: Discussionmentioning
confidence: 99%